Assessing the role of Islamic microfinance: a women empowerment case study: Assessing the role of Islamic microfinance - Senghore, Aja Fatou (European Journal of Islamic Finance, 2023)
The main objectives of this paper are three-fold. First, to identify the barriers to financial independence of female vegetable producers in the Gambia. Second, to assess the potential use of Islamic financing modes as enablers that can capacitate women in the Gambia’s horticultural sector. Finally, it proposes an inclusive financing mode to empower women in the country’s horticultural sector. To achieve these three objectives, different methodological approaches were used, drawing on various data collection techniques, including primary and secondary data collection methods. The results from the study indicate that lack of irrigation and storage facilities, access to markets and farming inputs (seeds, fertilisers) are the main challenges women encounter in their gardening activities. The study further found that the benefits of accessing and using microfinance services are impeded by these challenges, thereby preventing women vegetable producers from upscaling their horticultural activities. However, it is established in the paper that microfinance has great potential for promoting the financial independence of women in the Gambia, particularly women who engage in the horticultural sector. Based on these findings, the paper recommends using Parallel Salam Contract to tackle the problems of irrigation, storage facilities and market access. Murabahah/Musawamah contracts are also suggested to tackle the issue of the lack of farming inputs used by women in the horticultural sector. We further recommend that Islamic financial institutions educate the public about their business activities and for the regulators, including the Central Bank of the Gambia, to establish a Central Shari’ah Board to ensure the unification of fatwahs in the emerging Islamic finance sector in the Gambia, thereby ensuring transparency in the activities of the financial institutions participating in this sector and thus encourage more investors to partake in this burgeoning part of the Gambian economy.